Impact of financial inclusion and government policies on women entrepreneurs development in West Nusa Tenggara, Indonesia - Ulfa Amani Hidayati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Financial Inclusion is one of the government's efforts to increase economic growth just after the Covid Pandemic. Covid has caused economic harm. This highlights the importance of government policy in assisting all aspects of society, particularly entrepreneurs. This study focuses on women who own MSMEs. This is because women manage the majority of MSMEs in Indonesia. This study's data were gathered through questionnaires distributed to respondents. The data in this study were analysed quantitatively using multiple linear regression analysis. The Statistical Product and Services Solution (SPSS) application were used to analyze data in this study. Financial inclusion and government policies influence women entrepreneur development. To achieve economic development through MSMEs, it is hoped that future academics will investigate additional factors influencing the growth of female entrepreneurs in various regions of Indonesia.